Post-Traumatic Headache - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
The occurrence and persistence of headache after closed head injury was investigated in 129 children, 70 boys and 59 girls, during a follow-up period, average 5.9 yrs., in the Depts of Neuropsychology and Child Neurology, State University Hospital, P.O. Box 9600, 2300 RC Leiden, The Netherlands.